Preliminary Analysis of Precise Levelling Network for The Southern Peninsular Malaysia - Abu, Samad; A. Kadir, Abd. Majid; Ses, Shahrum (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
Precise levelling has been planned and implemented by the Department of Surveying and Mapping Malaysia (DSMM) for the provisioning of the levelling framework of the country. The precise levelling network provides the vertical reference datum for mapping and engineering purposes as well as for scientific research work, which includes tectonic movement monitoring and mean sea level studies. At present, twelve loops of precise levelling which cover the southern part of the Peninsular Malaysia were surveyed, processed and adjusted. The precise levelling was made with high precision levelling instruments which are currently used by DSMM, namely, Zeiss NI002A and digital automatic level, Wild NA3000. These instruments are capable of storing data in computer readable form for the purpose of processing and adjustment. Data acquired from the field were processed by RAPC-1 and DELTA processing software. Adjustment and analysis were made using Geolab network adjustment software. For future investigations on Peninsular Malaysia Height Datum, the levelling network has been tied to first order GPS network and tide gauge" stations. This paper briefly described the procedures for the acquisition, processing and adjustment of the levelling data for the twelve levelling loops covering the southern half of Peninsular Malaysia.